Quantitative characterization of multi-phase materials by digital image processing - Silva, F. D.; Hein, LRD; Ammann, J. J.; Nazar, AMM (Carl Hanser Verlag, 1998)
An automatic image processing and analysis technique has been developed for quantitative characterization of multi-phase materials. For the development of this technique is used the Khoros system that offers the basic morphological tools and a flexible, visual programming language. These techniques are implemented in a highly user oriented image processing environment that allows the user to adapt each step of the processing to his special requirements.To illustrate the implementation and performance of this technique, images of two different materials are processed for microstructure characterization. The result is presented through the determination of volume fraction of the different phases or precipitates.